2006
DOI: 10.1016/j.cardiores.2006.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Importance of recruitment of bone marrow-derived CXCR4+ cells in post-infarct cardiac repair mediated by G-CSF

Abstract: Recruitment of CXCR4+ cells into infarcted myocardial tissues via stimulation of the CXCR4/SDF-1 axis plays a critical role in the beneficial effects of G-CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 28 publications
5
63
0
Order By: Relevance
“…G-CSF is also efficient in inducing the mobilization of angiogenic BM cells, including CD34 + CD133 + VEGFR2 + EPCs, in addition to directly promoting angiogenesis, in part by upregulating SDF-1 [75][76][77]. The promising efficacy of G-CSF in supporting organ regeneration in animal studies is currently being tested in clinical trials [78].…”
Section: Delivery Of Sdf-1 For Stem Cell Therapy and Organ Revascularmentioning
confidence: 99%
“…G-CSF is also efficient in inducing the mobilization of angiogenic BM cells, including CD34 + CD133 + VEGFR2 + EPCs, in addition to directly promoting angiogenesis, in part by upregulating SDF-1 [75][76][77]. The promising efficacy of G-CSF in supporting organ regeneration in animal studies is currently being tested in clinical trials [78].…”
Section: Delivery Of Sdf-1 For Stem Cell Therapy and Organ Revascularmentioning
confidence: 99%
“…SDF-1 released from a myoblast sheet could mobilize CXCR4+ cells to the injured myocardium [2]. Moreover, stem-cell mobilization and homing therapy by G-CSF was introduced to another myocardial regeneration treatment as an alternative to cellular cardiomyoplasty [73,74].…”
Section: Paracrine Effect Of Cytokines After Cellular Cardiomyoplastymentioning
confidence: 99%
“…These authors reported that even though c-kit + increased from 0.05 to 2.8% in peripheral blood, growth factor treated mice did not improve their cardiac function performance, or decreased MI size or any sign of cardiac regeneration as well as cell therapy. Until that time, the mechanism of G-CSF action was discussed exclusively by increasing cell mobilization and homing to ischemic heart with conflicting results [6,8,[10][11][12][13].…”
Section: Pre-clinical Experimentsmentioning
confidence: 99%